Lives matter. Do votes? Invited commentary on "Black lives matter: Differential mortality and the racial composition of the U.S. electorate, 1970-2004". (July 2015) - Purtle, Jonathan
Abstract: Racial health disparities in the United States are produced and perpetuated through public policies that differentially allocate risks and resources for health. Elected officials have the ability modify the structural determinants of racial health disparities through policy decisions and, through voting, the electorate can influence the extent to which these policy decisions promote health equity. In this commentary, I synthesize research on the voting behavior of electorates and policy decisions and present strategies to foster sociopolitical environments that are conducive to the implementation and enforcement of racial health disparity reduction initiatives. There is a need for research that contributes to a more comprehensive understanding of the role of voting in health policy making processes and further development of empirically-based policy advocacy strategies.